THE EFFECT OF INSTITUTIONAL OWNERSHIP TO VOLUME REACTION AROUND EARNINGS ANNOUNCEMENTS AT THE JAKARTA STOCK EXCHANGE - Yuniasih, Rafika (Jurnal Akuntansi dan Keuangan Indonesia, 2005)
This study examines trading volume reaction to earnings announcements; specifically the effect of information asymmetry across investors before earnings announcement, in the form of differences in ownership structures measured by the level of institutional ownership, to trading volume around earnings announcements. Further, this study also examines other factors related to volume reaction around earnings announcements such as price changes resulted in certain unexpected earning levels, cost of transactions, and firm size. The Ordinary Least Square (OLS) method is initially used in finding the relation between unexpected trading volume in two-day and seven-day announcement period windows to the independent variables used in this study. Further, this study applies the Weighted Least Square (WLS) method to eliminate the potential heteroscedasticity and to increase efficiency of the model. This study finds that institutional ownership level as a measure of information asymmetry across investors affects volume response to earnings announcement. The study finds that trading volume reaction is an increasing function of the level of information asymmetry. The study also finds that trading volume reaction is an increasing function ofprice changes and firm size, yet it has a negative relation to transaction costs